Disease Ecology Galapagos Birds and their Parasites (Social and Ecological Interactions in the Galapagos Islands,, 2018)
This book provides the first collection of chapters written by scientists who have contributed to the understanding of disease ecology in the Galapagos Islands, an iconic and historic natural site. The Galapagos Archipelago straddles the equator in the eastern Pacific Ocean, almost 1000 km off the coast of Ecuador, and includes 13 major islands, numerous smaller satellite islands, and many more even smaller islets. The wildlife on the Galapagos Islands today represents one of the best-preserved wild communities of plants and animals in the world, owing to the location of the islands at the intersection of major ocean currents, the commitment by Ecuador for the vast majority of the area to be left undeveloped, and the protection provided by the Galapagos National Park. Most of the animal species in Galapagos are endemic, occurring nowhere else. But they are descendants of ancestors that colonized earlier, and then, isolated from their mainland origins, evolved into forms that are recognized as distinct today. Since 2001, many of the authors in this book have been part of a four-institution partnership investigating the threats posed by pathogens to Galapagos avifauna. We approach the topic of disease ecology in a novel manner, starting with the history of arrival of both the birds themselves and the pathogens. This synthetic approach requires the integration of themes from veterinary medicine, epidemiology, population genetics, and phylogenetics.